2019
DOI: 10.5935/0946-5448.20190014
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss and Alzheimer?s disease: A Review

Abstract: Many studies have focused on the relationship between hearing loss and Alzheimer's Disease (AD). The mechanisms and causal relationship of this association are still partially unknown, and several theories have been proposed. The most accredited hypothesis is that peripheral hearing deprivation may lead to social isolation and subsequently to dementia. Another hypothesis supports the role of hearing loss on cortical processing, with an increased assignment of cognitive resources to auditory processing rather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 68 publications
2
38
0
Order By: Relevance
“…In line with the literature, we found a higher incidence of AD in subjects with hearing loss. It has been widely associated in the literature with the risk of AD [51] and all-cause dementia [52], and several hypotheses about such causal relationship have been proposed. Among them, it is hypothesized that it could lead to social isolation, and this to dementia [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the literature, we found a higher incidence of AD in subjects with hearing loss. It has been widely associated in the literature with the risk of AD [51] and all-cause dementia [52], and several hypotheses about such causal relationship have been proposed. Among them, it is hypothesized that it could lead to social isolation, and this to dementia [51].…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely associated in the literature with the risk of AD [51] and all-cause dementia [52], and several hypotheses about such causal relationship have been proposed. Among them, it is hypothesized that it could lead to social isolation, and this to dementia [51]. In addition, it has been shown that the genetic risk of AD also influences the hearing of speech in noise, without these hearing deficits being related to further cognitive impairment [53].…”
Section: Discussionmentioning
confidence: 99%
“…Several other theories have been proposed to explain the association between hearing impairment and AD. Hearing impairment has been proposed as a risk factor for AD through mediating pathways such as sensory deprivation and social isolation leading to decreased cognitive function 15,50,51 and an increased cognitive load through auditory processing rather than other cognitive processes 52,53 . This decreased auditory stimulation may lead to micro‐changes in the brain that increase risk of AD brain pathology, such as amyloid decomposition 18 .…”
Section: Discussionmentioning
confidence: 99%
“…This decreased auditory stimulation may lead to micro‐changes in the brain that increase risk of AD brain pathology, such as amyloid decomposition 18 . An alternative hypothesis is that the relationship between these two traits may be due to a common cause, such as shared genes or age‐related changes in the brain, and that hearing impairment may be an early symptom of cognitive decline 2,53 …”
Section: Discussionmentioning
confidence: 99%
“…Several recent review studies have emphasized the maladaptive plasticity of NIHL, covering detailed neuronal aspects of triggers of tinnitus, mechanisms underlying generation of tinnitus in the cochlear nucleus after noise-induced deafferentation, likely routes of transmission of tinnitus signals along the ascending nuclei, as well as treatment approaches to reduce the impact of tinnitus on the quality of life of affected individuals [ 21 , 36 , 37 , 38 , 39 ]. A general consensus is that NIHL is preventable and that there is much more to learn about tinnitus and its underlying mechanisms and undisputed connection with NIHL.…”
Section: Overview Of Current Knowledgementioning
confidence: 99%